Principle of the best interests of the child: Difficulties surrounding its application in Chilean legislation (2019)
This paper takes a look at the principle of the best interest of children and adolescents in Chilean legislation, and the difficulties and peculiarities that it presents when the courts apply it in the resolution of conflicts submitted to their judgement. Through both interpretative and concrete criteria and tools, the courts have managed to provide it with specific content in order to achieve adequate protection in accordance with the mandate by national legislation. The criteria used to that effect will be analyzed both dogmatically and analytically, in order to specify the fuzzy limits of this principle.